KAPITALISASI PEMBANGUNAN KOTA DI RIAU (PERSPEKTIF EKONOMI POLITIKINFRASTRUKTUR) - Muchid Albintani (JIP ( Jurnal Industri dan Perkotaan ), 2010)
This article aim to analyse program development of phisical infrastucture as especial policy bases goverment Riau Province. Implication of excecution of the policy create constuction capitalization